STRATEGI PEMASARAN MELALUI PEMANFAATAN MEDIA SOSIAL PADA SANTANA SHOP (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
The purpose of this study is to determine the level of sales before and after using social media, to determine the factors that influence the increase in sales through social media, to know the marketing strategy so as to increase online salesin Santana Shop. The method of analysis in this study using SWOT analysis.The results of this study can be seen that the factors that affect the level of sales before and after using social media, among others, before using social media Santana Shop using offline and active store CFD in Purworejo square, after activein social media sales increased. Factors that affect the increase in sales through social media that is, social media can find out more about customers, develop target markets, reach the business, increase promotion. So by using SWOT analysis obtained strategy Strength-Opportunity that is, sale without capital with price of goods offered cheaper, give bag or wallet free, give discount, goods always update,follow event, social media make easy to sell, for dropship. Weakness-Opportunity Strategy is to increase online sales to reduce the workload, in cooperation with many gyro services, open resellers, create their own brand bags or wallets,Strength-Treath strategy that is, create 2 SIM cards, actively pro mote in social media networking, the more many create discount events, deliver exciting advertisements by multiplying new model updates, emerging new competitors at cheaper rates, providing original photo captions, Weakness-Treath strategy thatis, providing cheap rates from other stores, delivering inexpensive shipping services, opening online good resellers or offline.